adis Misoginis dalam Perspektif Hermeneutika Fatima Mernissi - Sauda', Limmatus (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2014)
This paper attempts to offer a different understanding of the hadith misogynic. Some hadiths are commonly used as the theology reason by the elite of men to smooth out their importance will be examined again, at this time it uses the reading of Fatima Mernissi. Fatima Mernissi is a feminist and a sociologist at the same time. Her background will give a deep impact in her interpretation. She reads it by using a historical and methodological approach. Both of it also become a Mernissi’s hermeneutic. For methodological approach, Mernissi based on ‘Ulûm al-Hadîth that are reliable according to her, this is done when deciding on acceptance or rejection an hadith. For the understanding of hadith, Mernissi applies the historical and sosilogical approach. The purposes of this article are to know and also understand Mernissi’s hermeneutic hadith by reread some hadiths misogynic. Based on her interpretation in hadith misogynic, thispaper’s findingsindicate that hadith misogynic is not really hate women.